Gestión del proceso de adquisiciones y su efecto financiero en las instituciones bancarias - Carrillo Mantilla, Andrea Michelle (2021)
The general objective of this research project is to develop a methodology in order to optimize acquisition processes, which in turn generate positive financial effects in banking institutions. It is a research with a mixed approach, of a non-experimental, cross-sectional and field type. Descriptive and exploratory research. To collect the information, techniques such as the interview, the documentary review, the observation and the survey were used, using as the study population three banking entities belonging to ASOBANCA, whose names are kept anonymous at the request of the banking entities…………